Incidence of Long-Term Esophageal Dilation With Various Treatment Approaches in the Older Head and Neck Cancer Population - Green, Garrett; Kim, Ellen; Carmona, Ruben; Shen, Hanjie; Murphy, James D.; Mell, Loren K. (Frontiers in Oncology, 2018)
Purpose: Treatments for locoregionally advanced head and neck cancer (LAHNC) negatively impact swallowing function, but the long-term incidence of severe toxicity requiring esophageal dilation is not well-documented in the population. The aim of this study was to compare the incidence of long-term esophageal dilation across varying treatments for LAHNC. Methods and Materials: We identified 5,223 patients with LAHNC diagnosed from 2000-2009 in the SEER-Medicare database. We compared the incidence of esophageal dilation for surgery alone vs. surgery plus adjuvant radiotherapy (RT) and chemoradiotherapy (CRT) vs. definitive RT or CRT. Results: The cumulative incidence of esophageal dilation for all sites at 10 years, according to treatment group were as follows: CRT, 14% (95% confidence interval (CI), 12%-17%); definitive RT, 13% (95% CI, 10%-16%); surgery alone, 5% (95% CI, 3%-7%); surgery and CRT, 15% (95% CI, 11%-19%); surgery and adjuvant RT: 10% (95% CI, 8%-13%). There was no significant difference in the incidence of esophageal dilation between surgery plus adjuvant RT/CRT or definitive RT/CRT (p=0.37), but the incidence was significantly increased in both groups compared to surgery alone (p=0.003). On multivariable analysis, chemotherapy was associated with significantly increased incidence of esophageal dilation (HR 2.9, 95% CI 1.5-5.5, p<0.001) in oropharyngeal cancers. Conclusions: The incidence of esophageal dilation is similar in LAHNC patients undergoing RT with or without surgery. Chemoradiotherapy increases the long-term risk of esophageal dilation events over surgery alone.